T‐cell‐related skin inflammatory flareups with Th1 polarity in a patient with pseudoxanthoma elasticum - Samuel Rocour; Emeline Vinatier; Céline Fassot; Jonathan Dauvé; Agnès Toutain; Sabrina Fronteau; Marine Monnier; Laurence Preisser; Anne Croué; Olivier Le Saux; Alain Morel; Yves Delneste; et al. (Wiley, 2024)
Abstract Pseudoxanthoma elasticum (PXE) is a genetic disorder characterized by ectopic calcification of tissues rich in elastic fibres (OMIM 264800). To date, PXE is considered a metabolic disease linked to an imbalance between pro‐ and anti‐calcifying factors. The occurrence of sporadic erythematous flareups of PXE skin lesions is a complaint that we heard about on several occasions at the French PXE reference centre. However, this rare clinical aspect had never been extensively studied. We have had the opportunity to investigate a 13‐year‐old patient experiencing an erythematous flareup of his PXE lesions. We conducted this work to identify what type of inflammation was implicated in his lesions. An incisional skin biopsy on a recent erythematous inguinal PXE lesion was performed and sent for histological and transcriptomic analyses. The findings were compared to a non‐erythematous PXE‐affected skin biopsy obtained from another young PXE patient. Histological examination revealed perivascular T‐cell infiltrates with Th1 polarity and elevated expression of cytotoxicity markers in RNAseq and RT‐qPCR analyses. There was no increase in Th17 or Th2 markers. Our findings support the previous evidence of a possible inflammatory component in the development of PXE. Whether Th1‐dependent inflammation contributes to the pathology as an active process or is an aggravating factor requires further investigations.